HUBUNGAN PEMBERIAN REWARD AND PUNISHMENT DENGAN MOTIVASI BELAJAR SISWA KELAS IV - Nur Azizah Ramadhani; mujahidah mujahidah; Rukayah Rukayah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
Low student learning motivation requires teachers to find ways to increase student learning motivation in order to achieve educational goals. One way that can be used is by applying reward and punishment in the learning process. This research is a correlational quantitative research with ex-post facto method. This research was conducted at SDN 42 Waetuwo with a sample of all fourth grade students, totaling 33 students. The results showed that the provision of reward and punishment to fourth grade students at SDN 42 Waetuwo was included in the good category with a percentage of 78.31% while learning motivation was included in the very good category with a percentage of 83.72%. And based on the results of inferential statistical analysis, the degree of relationship between the two variables was 37.45%, and the value of tcount = 4.307 was greater than the value of ttable = 1.69552 at a significance level of 5%. Thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between the provision of reward and punishment with the learning motivation of fourth grade students Bone Regency.